Functional Outcome Comparison of Free Gracilis Muscle Anchoring Methods in Patients with Facial Paralysis: Upper Lip Red Line Incision versus Facelift Incision Approach - Park, Hojin; Hong, Dae Won; Oh, Tae Suk (Journal of Reconstructive Microsurgery, 2022)
Background The greatest challenge of a free-muscle transfer in facial reanimation surgery is anchoring muscle to perioral soft tissue. An additional incision provides a better way to anchor the transferred muscle but leaves a visible scar. Herein, we compared the functional and aesthetic outcomes in a conventional facelift incision approach with and without the addition of a red line incision.Methods This study included patients experiencing unilateral facial paralysis who underwent free gracilis transfer between December 2016 and December 2018. Anchoring through facelift incision with extended neck incision was performed in the control group, while a red line incision was added in the red line group by avoiding extended neck incision. Oral commissure excursion, upper lip and commissure height differences, and symmetry were measured.Results A total of 24 patients met the criteria and were included in this study. Of these, 10 patients were assigned to the red line group and 14 to the control group. The red line and control groups demonstrated a similar symmetry index in both resting (0.96 ± 0.18 and 0.92 ± 0.10, respectively; p = 0.435) and smiling (0.94 ± 0.12 and 0.91 ± 0.10, respectively; p = 0.314). However, the upper lip height difference demonstrated greater postoperative improvement (resting: 2.12 ± 1.13 vs. 3.92 ± 1.41 mm, p = 0.002, and smiling: 1.68 ± 0.88 vs. 3.41 ± 1.69 mm, p = 0.004, respectively). A scar could be easily concealed on the mucocutaneous line of the lip.Conclusion This novel method for muscle anchoring in facial reanimation surgery allows surgeons to approach perioral muscle more directly. This leads to improved surgical results by securely anchoring the transferred muscles using a fixation point that is more medially located than in other approaches. Our method is effective and offers an improved surgical outcome for the free functional gracilis muscle transfer.
Keywords: facial paralysis; gracilis muscle; facial asymmetry; facial expression